2007
DOI: 10.1016/j.bbadis.2006.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent perinatal lethality of Ovol1-deficient mice and identification of Ovol2 as a downstream target of Ovol1 in skin epidermis

Abstract: Ovol1 encodes a zinc finger transcriptional repressor that is downstream of the LEF1/beta-catenin complex, nuclear effectors of canonical Wnt signaling. Previous gene knockout studies performed in a 129SvxC57BL/6 mixed genetic background revealed that Ovol1-deficient mice survive to adulthood but display multiple tissue defects. In this study, we describe a C57BL/6 strain-specific reduction in perinatal survival of Ovol1 mutant mice. The perinatal lethality is accompanied by kidney epithelial cysts of embryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
3
50
0
2
Order By: Relevance
“…Several explanations for this discrepancy can be forwarded. First, developmental processes often involve threshold effects that can be influenced by the genetic background: the literature is rife with examples of null mutations in mice that cause lethal defects on one inbred background, but which are relatively harmless on another (LeCouter et al, 1998;Becker et al, 2003;Teng et al, 2007). In this context, the lack of a phenotype in Fgfrl1 +/-mice may recapitulate…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations for this discrepancy can be forwarded. First, developmental processes often involve threshold effects that can be influenced by the genetic background: the literature is rife with examples of null mutations in mice that cause lethal defects on one inbred background, but which are relatively harmless on another (LeCouter et al, 1998;Becker et al, 2003;Teng et al, 2007). In this context, the lack of a phenotype in Fgfrl1 +/-mice may recapitulate…”
Section: Discussionmentioning
confidence: 99%
“…Ovol1 is predominantly expressed in suprabasal cells, whereas Ovol2 is predominantly expressed in basal cells. However, our previous analysis of Ovol1/Ovol2 compound mutants has provided evidence for possible functional redundancy and compensation between the two Ovol genes in an in vivo setting (17). Sharing a common molecular target offers a partial explanation for this observation.…”
Section: Molecular Mechanism Of Ovol2 Function In Controlling Keratinmentioning
confidence: 99%
“…Consistent with a widespread expression pattern, ablation of the Ovol2 gene results in early embryonic lethality (16), which precludes a comprehensive analysis of its later developmental roles. Interestingly, Ovol2 expression appears to correlate with a proliferative stem/progenitor cell state (16,17). For instance, Ovol2 protein is detected in the basal layer of skin epidermis (17), where proliferative epidermal stem/progenitor cells reside.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This process is tightly regulated, and disruption of epidermal differentiation characterizes epidermal cancers and common skin disorders, such as psoriasis and chronic wounds. Recent studies have identified regulators of epidermal differentiation, including the transcription factors KLF4 (Segre et al 1999;Patel et al 2006), OVOL1 (Teng et al 2007), and GRHL3 (Yu et al 2006;Hopkin et al 2012) and the chromatin regulators JMJD3 (Sen et al 2008) and BRG1/BRM (Indra et al 2005;Bao et al 2013). Transcription factors often interact with other transcription factors and chromatin regulators to enable specific, context-dependent gene activation or repression.…”
mentioning
confidence: 99%